Impact of audit committee quality on the financial performance of conventional and Islamic banks - Achraf Haddad; Anis El Ammari; Abdelfattah Bouri (Journal of Risk and Financial Management, 2021)
A lot of previous research studied the relationship between audit committee quality and the financial performance of conventional banks before and during the subprime crisis, whereas some other investigations analyzed the same association in the framework of Islamic banks. However, no study has compared these two correlations either before, during, or after the subprime crisis. Several reasons explain the differences, such as the audit committee quality of each bank type, the evaluation method of the financial performance, the research peculiarities, the methodology, the data, and the interpretation. This research aims to compare the impacts of the audit committees' quality on the financial performance of Islamic and conventional banks between 2010 and 2019. The financial performance measures and audit committees' determinants of the conventional and Islamic banks concerned 112 banks of each type. The collected data covered four continents: America, Asia, Africa, and Europe. Impacts were compared by using the Generalized Least Squares analysis. The results showed that the audit committee reduced the profitability of two bank types. Moreover, it harmed the conventional banks' efficiency but reported an unclear effect within Islamic banks. Even so, we noticed that the audit committee had a positive impact on the conventional banks' liquidity, while the same effect was apparently ambiguous for the Islamic banks' liquidity. For solvency, the audit committee positively influenced conventional banks while it affected that of Islamic banks.
Keywords: 330; audit committee (AC); audit committee quality (ACQ); comparative study; conventional banks (CBs); financial performance (FP); financial stability period; Islamic banks (IBs)